A review study on application of gel dosimeters in low energy radiation dosimetry. (January 2022) - Alyani Nezhad, Zahra; Geraily, Ghazale
Abstract: Introduction: The accuracy of dose delivered to tumors and surrounding normal tissues is vital in either radiotherapy using low energy photons and radiological techniques as well as radiotherapy with mega voltage energies. This systematic review focuses on applications of gel dosimetry in low energy radiation contexts applied either through radiotherapy or interventional radiology. Methods: Literature was reviewed based on electronic databases: Google Scholar, Scopus, Embase, PubMed, Science Direct, Research Gate and IOP science. The search was conducted on relevant terms in the title and keywords. 82 articles related to our criteria has been extracted and included in the study. Results: The findings demonstrated that almost all types of gel dosimeters had an acceptable accuracy and high resolution in low energy radiation contexts with their own limitations and advantages. Conclusion: Gel dosimeters compete well with other conventional dosimeters in terms of tissue equivalence and energy dependence; however, choosing the best gel dosimeter for use in low energy radiation dosimetry depends on their different limitation and advantages. There are some general features about each gel group which can help to select the suitable gel related to our work. For example, methacrylic acid based gel dosimeters show higher sensitivity compared to other types of gel dosimeters but have more toxicity and are dose rate dependent in the range of dose rates applied in low energy contexts. In addition, Fricke gel dosimeters exhibit less sensitivity while they are independent of dose rate and energy applied in low energy situations. Highlights: Polymer gels have wide dose dynamic range of about 250 Gy. Most polymer gels are energy dependent in energies lower than 60 KeV. GENIPIN gel has better water equivalency for energies lower than 60 KeV. There are differences in gel response from one formulation to another. Choosing the best gel dosimeter depends on their different characteristics.